Association between diabetes mellitus and primary biliary cholangitis: a two-sample Mendelian randomization study - Lv, Dan; Wang, Han; Leng, Yan; Chen, Sitong; Sun, Haitao; Meng, Xiangyue; Liu, Tiejun; Xiong, Zhuang (Frontiers in Endocrinology, 2024)
Background: Previous observational studies have demonstrated a link between diabetes mellitus(DM) and primary biliary cholangitis (PBC). Nevertheless, since these relationships might be confused, whether there is any causal connection or in which direction it exists is unclear. Our investigation aimed to identify the causal associations between DM and PBC.We acquired genome-wide association study (GWAS) datasets for PBC, Type 1 diabetes(T1DM), and Type 2 diabetes(T2DM) from published GWASs. Inverse variance-weighted (IVW), MR-Egger, weighted median (WM), Simple mode, and weighted mode methods were used to determine the causal relationships between DM( T1DM or T2DM ) and PBC. Sensitivity analyses were also carried out to ensure the results were robust. To determine the causal relationship between PBC and DM( T1DM or T2DM ), we also used reverse MR analysis.Results: T1DM was associated with a higher risk of PBC (OR 1.1525; 95% CI 1.0612-1.2517; p = 0.0007) in the IVW method, but no evidence of a causal effect T2DM on PBC was found (OR 0.9905; 95% CI 0.8446-1.1616; p = 0.9071) in IVW. Results of the reverse MR analysis suggested genetic susceptibility that PBC was associated with an increased risk of T1DM (IVW: OR 1.1991; 95% CI 1.12-1.2838; p = 1.81E-07), but no evidence of a causal effect PBC on T2DM was found (IVW: OR 1.0101; 95% CI 0.9892-1.0315; p = 0.3420).The current study indicated that T1DM increased the risk of developing PBC and vice versa.There was no proof of a causal connection between PBC probability and T2DM. Our results require confirmation through additional replication in larger populations.